1997
DOI: 10.1212/wnl.48.6.1704
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy of human malignant glioma

Abstract: Steroids are commonly administered for the control of edema, mass effect, and side effects from therapy to patients with malignant glioma who are receiving radiotherapy and chemotherapy. Here, we report that therapeutic concentrations of dexamethasone (DEX) attenuate cytotoxicity and growth inhibition of human malignant glioma cells induced by exposure to several chemotherapeutics, including ACNU, VM-26, vincristine, cytarabine, methotrexate, and adriamycin. DEX-mediated cytoprotection is not linked to DEX eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(48 citation statements)
references
References 0 publications
1
46
1
Order By: Relevance
“…The general procedure has been described, 51 including the preparation of cytoplasmic lysates for the detection of Cyt c from mitochondria. 49 The following antibodies were used: anti-XIAP, anti-RIAP-1, -2 and -3, 52,53 …”
Section: Immunoblot Analysismentioning
confidence: 99%
“…The general procedure has been described, 51 including the preparation of cytoplasmic lysates for the detection of Cyt c from mitochondria. 49 The following antibodies were used: anti-XIAP, anti-RIAP-1, -2 and -3, 52,53 …”
Section: Immunoblot Analysismentioning
confidence: 99%
“…19 Several years ago, it was shown that the use of steroids influences vascular response to radiation 20 and directly inhibits apoptosis in human malignant glioma cells. 21 However, in spite of strong efforts, an adequate replacement medication for dexamethasone has not been found yet. Boswellic acids could be the basis for a new kind of anti-inflammatory and thus antiedema medication with decreased adverse effects, the additional induction of apoptosis, and no modulation of drug (and radiation) sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, more and more data from preclinical studies, and to some extent from clinical studies, have strongly recommended a GC-conferred resistance to cancer therapy in the majority of malignant solid tumors -irrespective of tumor origin and the nature of specific anticancer drugs (Wolff et al 1996, Weller et al 1997, Webster et al 2002, Herr et al 2003, Wu et al 2004, Gassler et al 2005, Runnebaum & BrĂźning 2005, Sui et al 2006, Zhang et al 2006a,b,c,d,e, 2007. In this study, we have demonstrated that Dex could protect human ovarian IgG (10 Âľg/ml) Anti-β1 (Âľg/ml) Figure 4 Dex-enhanced cell attachment and cell survival are partially reversed by integrin b1-blocking antibody.…”
Section: Discussionmentioning
confidence: 99%
“…More recent data indicate that GCs can inhibit apoptosis induced by chemotherapy not only in established cancer cell lines and tumor xenografts, but also in the freshly isolated cells from surgical resections from tumors of various origins, including ovary, breast, prostate, pancreas, liver, colon, brain, cervix, bone, skin, and nervous system (Herr et al 2003, Sui et al 2006, Zhang et al 2006a. In addition, the anti-chemotherapeutic effect of GCs can be seen in several anticancer drugs including cisplatin (Wolff et al 1996, Gassler et al 2005, Zhang et al 2006a,b,d, 2007, paclitaxel (Wu et al 2004, Sui et al 2006, 5-fluorouracil (Zhang et al 2006a(Zhang et al , 2007, adriamycin (Weller et al 1997), actinomycin D (Wolff et al 1996), doxorubicin (Wu et al 2004), and gemcitabine (Gassler et al 2005, Zhang et al 2007). The GC-induced pro-survival effects should be of important clinical relevance when they interfere with the effect of chemotherapeutics.…”
Section: Introductionmentioning
confidence: 99%